Chronic Pseudoaneurysm and Anterior Dislocation After Total Hip Arthroplasty Complicated by Arterial Injury: A Case Report. Issue 2 (25th April 2022) - Crown, Taylor J.L.; Sheridan, Gerard A.; Bengoa, Francisco; Fransen, Bas L.; Lawlor, David K.; Clarkson, Paul W.; Greidanus, Nelson V.
Abstract : Case: A 64-year-old man presented 18 months after total hip arthroplasty complicated by vascular injury with a history of leg pain, inability to mobilize, and progressive chronic leg edema. It is presumed that there was persistent subtle bleeding over time with pseudoaneurysm formation and prosthetic hip dislocation secondary to the mass effect. Conclusion: Physicians should consider pseudoaneurysm as a possible diagnosis when confronted with a large intra-articular mass in the hip after a relatively short follow-up period, particularly in the context of a prior vascular injury at the time of the index procedure.